TASTE TRUMPS HEALTH AND SAFETY: INCORPORATING CONSUMER PERCEPTIONS INTO A DISCRETE CHOICE EXPERIMENT FOR MEAT. (30th January 2017) - MALONE, TREY; LUSK, JAYSON L.
Abstract: Consumers implicitly incorporate their perceptions of products into their decision processes, yet little research has explicitly focused on how those perceptions influence demand for meat. This study incorporates taste, health, and safety perceptions into a discrete choice experiment for meat products at a grocery store. Our results indicate that taste is the most important perception as a 1-unit increase in the perceived tastiness (on a −5 to +5 scale) of a food product leads to a 0.60 increase in willingness to pay, whereas equivalent increases in perceived health and safety lead to 0.31 and 0.21 increases, respectively.